Are repeated assisted reproductive technology treatments and an unsuccessful outcome risk factors for unipolar depression in infertile women?. (3rd August 2015) - Sejbaek, Camilla S.; Pinborg, Anja; Hageman, Ida; Forman, Julie L.; Hougaard, Charlotte Ø.; Schmidt, Lone
Abstract: Introduction: Previous studies have shown conflicting results as to whether unsuccessful medically assisted reproduction is a risk factor for depression among women. This study therefore investigated if women with no live birth after assisted reproductive technology (ART) treatment had a higher risk of unipolar depression compared with women with a live birth after ART treatment. Material and methods: The Danish National ART‐Couple (DANAC) Cohort is a national register‐based cohort study that consists of women who received ART treatment from 1 January 1994 to 30 September 2009, in Denmark ( n  = 41 050). Information on unipolar depression was obtained from the Danish Psychiatric Central Research Register. The analyses were conducted in Cox regression analysis. Results: During the 308 494 person‐years of follow up, 552 women were diagnosed with unipolar depression. A Cox proportional hazards model showed that women in ART treatment, with no live birth yet, had a lower risk of unipolar depression compared with women with a live birth. Women had the highest risk of unipolar depression 0–42 days after a live birth (adjusted hazard ratio 5.08, 95% CI 3.11–8.29) compared with women with no live birth. A lower, but still increased, risk of unipolar depression, was found in women 43 days to 1 year and >1 year after a live birth compared with women with no live birth yet. Conclusions: Motherhood is an important trigger of unipolar depression in women conceiving after ART treatment.